(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2023)
We believe that the wealth of digital humanity research resources that is available in Institutional Repositories in Southern Africa is largely over-looked because it is not machine explorable as defined by Berners-Lee (2006). We argue that extracting research from Institutional Repositories, which Berners-Lee (2006) describes as One-Star Linked Data, and then enriching this research and storing it as tuples in a triple store (RDF data store) will expose the research to a greater audience; make it machine explorable; and integrate it with a broader network of Linked Data, known as the Linked Open Data Cloud (LODC).Our approach is to utilize software building blocks licensed under Free (Libre) Open Source Software (FLOSS) licences and to create a pipeline that can potentially transform any Institutional Repository into into a triple store, which can be published onthe Internet as part of the LODC. Our transformation process embraces under-resourced institutions by utilizing FLOSS com-ponents and utilizing digital resources already published on the internet in order to promote the research from One-Star Linked data to Five-Star Linked Data in Berners-Lee (2006) taxonomy of linked data.